Purification and characterization milk-clotting aspartic proteinases from Centaurea calcitrapa cell suspension cultures - Raposo, Sara (2014)
Plant aspartic proteinases (APs) were isolated from several sources and studied for milk-clotting ability. Extraction of milk-clotting proteinases from intact plants is labor intensive and so, plant cell cultures is a viable alternative to obtain clotting enzymes. The aim of this work was to isolate APs from established suspension cell cultures of Centaurea calcitrapa and evaluate it's the potential interest for milk clotting. Plant cell extract was purified by ionic-exchange and hydrophobic-interaction chromatographies. Results suggest that the milk-clotting proteinases from cell cultures are synthesized as a 66-kDa proenzyme which originates a 50-kDa mature enzyme. The enzyme inhibition of 92% by pepstatin at 10 μM proved it to be an aspartate proteinase. The clotting time for purified APs suggests that these extracts may be used in the production of dairy products of weak paste or conjugated with other commercial rennets.